2008
DOI: 10.1159/000145327
|View full text |Cite
|
Sign up to set email alerts
|

Statin Potentiates Human Platelet eNOS Activity without Enhancing eNOS mRNA and Protein Levels

Abstract: Background/Aims: Experimental studies suggest an enhanced endothelial and platelet nitric oxide (NO) generation after statin treatment, possibly due to increased endothelial NO synthase (eNOS) activity and protein levels. In parallel with experimental research, statins were shown to increase the forearm blood flow independently of serum cholesterol in humans. However, it was not possible to correlate blood flow changes with eNOS levels in these studies due to limitations in obtaining arterial samples. Hence, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 99 publications
(82 reference statements)
1
11
0
Order By: Relevance
“…Because cerebrovascular tone and blood flow are mediated in part by eNOS (Morikawa et al, 1994;Yamada et al, 2000), the beneficial effects of BNP agonists on post-traumatic cerebral perfusion could be due to upregulation of eNOS; however, there are several mechanisms by which BNP may enhance eNOS activity without affecting RNA levels (Yemisci et al, 2008). As an example, HMG-CoA reductase inhibitors (statins) have been demonstrated to enhance eNOS activity acutely through post-translational modification, increasing NO generation by enhancing phosphorylation of eNOS by the protein kinase Akt, but not affecting mRNA levels .…”
mentioning
confidence: 99%
“…Because cerebrovascular tone and blood flow are mediated in part by eNOS (Morikawa et al, 1994;Yamada et al, 2000), the beneficial effects of BNP agonists on post-traumatic cerebral perfusion could be due to upregulation of eNOS; however, there are several mechanisms by which BNP may enhance eNOS activity without affecting RNA levels (Yemisci et al, 2008). As an example, HMG-CoA reductase inhibitors (statins) have been demonstrated to enhance eNOS activity acutely through post-translational modification, increasing NO generation by enhancing phosphorylation of eNOS by the protein kinase Akt, but not affecting mRNA levels .…”
mentioning
confidence: 99%
“…There is, however, consistent evidence of a benefit of statins when administered to rodent models of acute ischemic stroke, and of a dose-response effect on neuroprotection [6,7,8,9,10,11,12, 14]. There is some evidence that higher doses may have less benefit than lower doses when administered at 24 h after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical evidence suggest that by reducing downstream products of the mevalonate pathway other than cholesterol, statins can have beneficial effects on endothelial function, coronary and cerebral blood flow, inflammation, and hemostasis [4, 5]. More recently, experimental studies have demonstrated that several statins can reduce neuronal injury and infarct size in rodent models of acute ischemic stroke [6,7,8,9,10,11,12,13]. In these animal models, statins have been given both before the experimental stroke and as an acute treatment early (3 h) after the stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a comparative study between neonatal and adult models of rodent ischaemic stroke has shown that statin-mediated neuroprotection may somewhat be independent of eNOS modulation and be attributed to the pleiotropic effects of statins pertaining to inhibition of PKCa activity despite other recent studies revealing statinevoked significant simultaneous increases in endothelial cell Kruppel-like factor-2, a novel endothelial inflammation regulator and thrombomodulin expressions and platelet eNOS activity (Cimino et al 2005;Paumelle et al 2006;Yemisci et al 2008;Rossi et al 2010). …”
Section: No Donorsmentioning
confidence: 99%